Determinants of Breast Self-Examination Practices Among Female Vocational High School Students - Nathanya Abigail Hery Pengsin; Ola Meyasa (SIGn Journal of Public Health, 2025)
Breast cancer remains a global public health challenge with increasing morbidity, necessitating secondary prevention efforts as early as possible, particularly among adolescents. This study aims to analyze the relationship between knowledge, attitudes, and breast cancer early detection practices using the BSE method among female adolescents at SMKN 2 Palangka Raya. Methodologically, an analytical observational research design with a cross-sectional approach was employed. The sample consisted of 79 female students selected through purposive sampling. Primary data were collected via structured questionnaires and analyzed using the Chi-Square statistical test at a 5% significance level. Based on the results, univariate analysis revealed that most respondents (54.44%) had knowledge in the “fair” category and demonstrated highly positive attitudes toward BSE (73.42%). Nonetheless, field findings indicated that the majority of students (58.20%) had never practiced early detection. Bivariate testing proved a statistically significant relationship between knowledge and BSE practice (p=0.005). Conversely, no significant relationship was found between attitudes and these preventive practices (p=0.906). Consequently, it can be concluded that knowledge is the primary determinant driving students to perform self-examinations, whereas positive attitudes alone are insufficient to trigger actual practice without additional support. These findings recommend the need for health education innovation in schools, shifting from theoretical counseling to practical training using breast phantoms to bridge the gap between intention and optimal early-detection implementation.